Laboratory evolution of microalgae for food applications - Ho, Ivan Yan De (Nanyang Technological University, 2024)
With the increase in human population, there is an increase in demand for food. It is paramount to acquire for alternative food sources. Food application of microalgae is a sustainable way to overcome the various challenges of the growing population and environment sustainability. Our research explores the cultivation of chlorella sorokiniana, a freshwater microalga in salinity through laboratory evolution. The research performs UV and EMS mutagenesis of chlorella sorokiniana and cultivating them in salinity stress. The aim is to cultivate chlorella sorokiniana with the desirable phenotypes to survive in high salinity. Optical density readings and color pigments are parameters used to determine success of mutagenesis. Chlorella sorokiniana has the highest growth rate and biomass productivity in 0.3M of NaCl, followed by 0.5M of NaCl with the lowest in 0.4M of NaCl. Since the freshwater supply is depleting through the years, being able to cultivate microalgae in salinity environment helps to increase the sustainability of microalgae in food applications. Chlorella sorokiniana has high nutrients content, large scale cultivation in the laboratory helps to increase food supplies to combat the rising human population. Gene extractions and sequencing is recommended to improve the screening of chlorella sorokiniana with desired phenotypes.